NILAI-NILAI QUR’ANI DAN INTERNALISASINYA DALAM PENDIDIKAN - Farida, Umma (Pascasarjana IAIN Kudus, 2013)
Application of the noble values of religion that comes from the Qur’an in education is increasingly becoming a necessity, especially in thisera of globalization. Although the values and positive attitudes suchas honesty, patience, simplicity and generosity was also inheritedby genetic parents, but education and infrastructure that supportsthe process of internalization of those values must also be taken andprovided to form a Quranic generation.